2014
DOI: 10.3389/fpsyg.2014.00478
|View full text |Cite
|
Sign up to set email alerts
|

Mirror-image discrimination in the literate brain: a causal role for the left occpitotemporal cortex

Abstract: Previous studies show that the primate and human visual system automatically generates a common and invariant representation from a visual object image and its mirror reflection. For humans, however, this mirror-image generalization seems to be partially suppressed through literacy acquisition, since literate adults have greater difficulty in recognizing mirror images of letters than those of other visual objects. At the neural level, such category-specific effect on mirror-image processing has been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Exactly as teachers have refined, at an adult age, how they process children faces (de Heering & Rossion, 2008), the Braille readers we tested here learnt to break mirror invariance compulsory for Braille letters years after they started to break mirror invariance for Latin letters. Even more strikingly, the current results also favor the idea that the cortical representations underlying this perceptual bias can be reshaped to the point of not leading to any brain competition between the old and the novel material of expertise, presumably to facilitate efficient processing of the novel script (see Dehaene et al, 2010;Pegado, Nakamura, Cohen, & Dehaene, 2011; but see Nakamura, Makuuchi et al, 2014; for a review, see Pegado, Nakamura et al, 2014).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Exactly as teachers have refined, at an adult age, how they process children faces (de Heering & Rossion, 2008), the Braille readers we tested here learnt to break mirror invariance compulsory for Braille letters years after they started to break mirror invariance for Latin letters. Even more strikingly, the current results also favor the idea that the cortical representations underlying this perceptual bias can be reshaped to the point of not leading to any brain competition between the old and the novel material of expertise, presumably to facilitate efficient processing of the novel script (see Dehaene et al, 2010;Pegado, Nakamura, Cohen, & Dehaene, 2011; but see Nakamura, Makuuchi et al, 2014; for a review, see Pegado, Nakamura et al, 2014).…”
Section: Discussionsupporting
confidence: 67%
“…Third, it has been observed that the ability to break mirror invariance develops as a function of literacy, even if it is acquired at an adult age (Fernandes & Kolinsky, 2013;Kolinsky et al, 2011;Pegado, Comerlato et al, 2014). Fourth, both beginning child readers and adult fluent readers, but not preliterate children (Fernandes et al, 2016) or illiterate adults Nakamura, Makuuchi et al, 2014), break mirror invariance compulsorily and are therefore unable to ignore mirror-image differences even when this hinders performance (Dehaene et al, 2010;de Heering, Collignon, & Kolinsky, 2018;Fernandes et al, 2016;Pegado, Nakamura et al, 2014). In fact, only literates show a mirror cost when performing a speeded same-different orientation-independent comparison task, responding more slowly "same" to mirrored stimuli compared to strictly identical ones.…”
Section: Introductionmentioning
confidence: 99%
“…Mirror letter stimuli are specially processed by the left hemisphere (Pegado et al, 2011;Nakamura et al, 2014), and left hemisphere lesions sometimes affect reading and writing of mirror letters (Schott, 2007). LLF-damaged subjects therefore may have had particular difficulty tuning attention to the letter-shaped stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…However, the neurophysiological mirror-generalization process may lead this initial information on orientation being lost during memory transfer along the visual ventral occipito-temporal pathway (see [47] for more information about this pathway). As a result, there is a short period of time during which children master the shape of the characters but not their left-right orientation.…”
Section: A Theory Of Character Reversal In Writing From Memorymentioning
confidence: 99%